2019
DOI: 10.1016/j.tjem.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Rapid disappearance of pneumorrhachis after chest tube placement

Abstract: IntroductionWe present a rare case of traumatic pneumorrhachis with the combination of hemothorax which resolved rapidly after insertion of a chest tube.Case presentationA 55 year old male was admitted to our emergency department after falling from a ladder. His general condition was well, GCS was 15 with no motor deficits. On his spinal CT a fracture on multiple ribs leading to right sided hemothorax was observed with air in the T6-T8 spinal canal. A chest tube was placed and as he did not have any neurologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…1,10 Management of pneumorrhachis is mostly conservative with bed rest and treatment of any underlying cause. 1,10,17 Meningitis should also be suspected as a complication of PR. However, as shown by the systematic review conducted by Osunronbi et al, 1 there is not enough evidence supporting prophylactic antibiotic treatment as a means of preventing meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…1,10 Management of pneumorrhachis is mostly conservative with bed rest and treatment of any underlying cause. 1,10,17 Meningitis should also be suspected as a complication of PR. However, as shown by the systematic review conducted by Osunronbi et al, 1 there is not enough evidence supporting prophylactic antibiotic treatment as a means of preventing meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…Three cases have been reported with complete resolution of PRS on follow-up CT scan after 4 to 14 days. [5][6][7] The PRS is usually asymptomatic and an accidental finding on CT images while evaluating other severe or life-threatening torso injuries. Although CT is the gold standard for diagnosis, it is difficult to differentiate epidural and subarachnoid PRS.…”
Section: Discussionmentioning
confidence: 99%
“…1 In subarachnoid PRS, timely consultation with a neurosurgeon for decompression of nerve root injuries, tension pneumocephalus and exploratory surgery by a chest surgeon to detect severe thoracic trauma is vital. Impressively, Avci et al 5 reported a case of complete resolution of subarachnoid PRS on the fifth day of admission with recovery of neurological deficit after chest tube insertion. They concluded that the negative pressure of the chest drain to withdraw the air supported the hypothesis of a one-way valve mechanism in which high pressure air travels through fascial layers but is unable to return.…”
Section: Discussionmentioning
confidence: 99%